2013
DOI: 10.1111/jnc.12606
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic mutation of UBQLN2 impairs its interaction with UBXD8 and disrupts endoplasmic reticulum‐associated protein degradation

Abstract: Protein aggregation is a common feature of several neurodegenerative diseases, including amyotrophic lateral sclerosis (ALS) and frontotemporal lobar degeneration. How protein aggregates are formed and contribute to neurodegeneration, however, is not clear. Mutation of Ubiquilin 2 (UBQLN2) has recently been linked to ALS and frontotemporal lobar degeneration. Therefore, we examined the effect of ALS-linked UBQLN2 mutation on endoplasmic reticulum-associated protein degradation (ERAD). Compared to its wild-type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
50
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 28 publications
(46 reference statements)
5
50
0
Order By: Relevance
“…We speculate that this susceptibility is because they are vulnerable to disturbances in proteostasis, based on the defective properties of mutant UBQLN2 proteins and by extrapolation from other studies. First, our results, like those of others studies, clearly show the UBQLN2 mutants disrupt proteostasis, leading to accumulation of misfolded proteins (13,(28)(29)(30)(31). Second, accumulating evidence suggests disturbance in proteostasis, particularly induction of the UPR, as central in disease pathogenesis caused by ALS mutations in SOD1 and C9ORF72 (45)(46)(47)(48)(49).…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…We speculate that this susceptibility is because they are vulnerable to disturbances in proteostasis, based on the defective properties of mutant UBQLN2 proteins and by extrapolation from other studies. First, our results, like those of others studies, clearly show the UBQLN2 mutants disrupt proteostasis, leading to accumulation of misfolded proteins (13,(28)(29)(30)(31). Second, accumulating evidence suggests disturbance in proteostasis, particularly induction of the UPR, as central in disease pathogenesis caused by ALS mutations in SOD1 and C9ORF72 (45)(46)(47)(48)(49).…”
Section: Discussionsupporting
confidence: 64%
“…On the other hand, it could signify a loss of function, because UBQLN proteins function in autophagy, which typically involves clearance of large aggregates. Other studies have shown ALS-FTD UBQLN2 mutations reduce binding of UBQLN2 with its normal partners, suggesting a possible loss of function (19,22,28). Evidently, understanding how UBQLN2 mutations cause ALS-FTD is important for understanding the mechanisms underlying the disease and for developing novel pharmacotherapies to halt the disease.…”
Section: Als | Motor Neuron Disease | Ubqln2 | Tdp-43 Pathologymentioning
confidence: 99%
See 1 more Smart Citation
“…A possible explanation for this increase is that excessive amounts of ubiquilin-2 in cells might lead to uncoordinated binding of the protein to ubiquitinated proteins and/or the proteasome, disrupting proteostasis. Another possibility is that overexpression could lead to unregulated binding of ubiquilin-2 to its other partners, such as erasin, UBXD8, hnRNPA1 or with other ubiquilin proteins, all of which have been shown to bind ubiquilin-2 [9, 18, 20]. Such unregulated binding could interfere with either one or both of these protein functions, leading to toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent to this discovery several additional mutations in UBQLN2 have been reported [68]. However, the mechanisms by which any of the UBQLN2 mutations cause ALS is not known, although some initial studies of some of them suggest the encoded proteins might interfere with proteasomal degradation [5, 9, 10]. How the mutations interfere with proteasomal degradation is not clear as all of the UBQLN2 mutations described so far map in the central domain of the encoded ubiquilin-2 protein, but not in its surrounding functional ubiquitin-like (UBL) and ubiquitin-associated (UBA) domains, located at the amino-terminus and carboxyl-terminus, respectively [1113].…”
Section: Introductionmentioning
confidence: 99%